Dynamic relationship between house prices in Malaysias major economic regions and Singapore house prices - Fereidouni, Hassan Gholipour (Routledge, 2016)
Fereidouni H. G., Al-Mulali U., Lee J. Y. M. and Mohammed A. H. Dynamic relationship between house prices in Malaysia's major economic regions and Singapore house prices, Regional Studies. The purpose of this study is to examine house price diffusion among Malaysia's major economic regions (Kuala Lumpur, Selangor, Pulau Pinang and Johor) and between each of these regions and neighbouring Singapore by using the quarterly data from 2000:Q1 to 2011:Q1. By applying multivariate co-integration approach, the results show the existence of ripple effects among Malaysia's major economic regions. Moreover, it is found that house price diffusion observed within a country can be extended across the border. Implications are offered along with the findings of this research.